Психологія мас: функціональна значущість у соціальному конструюванні - Луценко, А. В. (ХНУРЕ, 2020)
The article deals with the mass type of consciousness, its specific features and factors, the mechanism that influences the emergence and development of spontaneous behavior and public opinion, the types of crowds and its main features, the mechanism of crowd breakup. Functional significance of psychology of masses and mass behavior. The role of the crowd in socially significant events
Keywords: філософія; психологія мас